2018
DOI: 10.1145/3137569
|View full text |Cite
|
Sign up to set email alerts
|

Toward Efficient Short-Video Sharing in the YouTube Social Network

Abstract: The past few years have seen an explosion in the popularity of online short-video sharing in YouTube. As the number of users continue to grow, the bandwidth required to maintain acceptable quality of service (QoS) has greatly increased. Peer-to-peer (P2P) architectures have shown promise in reducing the bandwidth costs; however, the previous works build one P2P overlay for each video, which provides limited availability of video providers and produces high overlay maintenance overhead. To handle these problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Chinese youth can only fulfil their mission and responsibilities in the new era by bolstering cultural self-confidence, fully reaffirming the value of an excellent, healthy cultural environment, and having absolute faith in its vitality. The gradual development of new media communication forms has opened up new possibilities for the dissemination of a positive cultural environment [1]. Short video is one of the mobile phone clients that is currently undergoing the most rapid development.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese youth can only fulfil their mission and responsibilities in the new era by bolstering cultural self-confidence, fully reaffirming the value of an excellent, healthy cultural environment, and having absolute faith in its vitality. The gradual development of new media communication forms has opened up new possibilities for the dissemination of a positive cultural environment [1]. Short video is one of the mobile phone clients that is currently undergoing the most rapid development.…”
Section: Introductionmentioning
confidence: 99%
“…PKI enables central authorities to offer verified credentials within the environments. 16 Shen et al 15 revealed the challenges in overcoming three PKI constraints depending on authentication mechanisms.…”
Section: Related Workmentioning
confidence: 99%
“…The corresponding test results are shown in Figure 3 and Table 4. The time cost was evaluated for specific encryption algorithms using (5,10,15,20,25) attribute values. The corresponding time cost remained constant at 21.71 ms, as shown in Table 3.…”
Section: Time Costmentioning
confidence: 99%
See 2 more Smart Citations